Cholesteryl Ester Species but Not Serum Proprotein Convertase Subtilisin/Kexin Type 9 Levels Decline in Male Patients with Active Inflammatory Bowel Disease - Angelika Hettenbach; Tanja Elger; Muriel Huss; Gerhard Liebisch; Marcus Höring; Johanna Loibl; Arne Kandulski; Martina Müller; Hauke Christian Tews; Christa Buechler (Pathophysiology)
Background/Objectives: Proprotein convertase subtilisin/kexin type 9 (PCSK9) regulates serum cholesterol levels and inflammation, both of which are dysregulated in inflammatory bowel disease (IBD). Free cholesterol (FC) and the various types of cholesteryl ester (CE) have different functions in the body. However, it is not yet known whether these lipids undergo parallel changes in male and female patients with active IBD, nor whether PCSK9 correlates with these lipids and disease severity in either sex. The present study measured the serum levels of PCSK9, FC, and 15 CE species in IBD patients, focusing on the associations of these molecules with sex, each other, and with disease severity. Methods: The serum PCSK9 levels of 80 IBD patients (42 males and 38 females) and 24 controls (12 males and 12 females) were measured by enzyme-linked immunosorbent assay. In addition, FC and 15 CE species levels of 53 randomly selected IBD patients and 16 controls were determined by direct flow injection analysis (FIA) using a high-resolution hybrid quadrupole-orbitrap mass spectrometer (FIA-FTMS). Results: Serum PCSK9 levels in controls and IBD patients were comparable and did not correlate with disease severity in IBD patients. There was no discernible difference in serum PCSK9, FC, and CE levels between patients with Crohn’s disease (CD) and those with ulcerative colitis (UC). FC and almost all CE species decreased in male patients with active IBD but were not related to disease severity in the female patients. The decrease in different CE species in male IBD patients with diarrhea compared to those with normal stool consistency appears to be related to IBD severity. Bile acids regulate serum cholesterol levels, and FC and CE levels were positively correlated with fecal levels of secondary bile acids in the patients with UC but not CD. This association also existed in male UC patients and could not be evaluated in women due to the small sample size. Conclusions: In active IBD, a reduction in FC and almost all CE species was observed only in males, while serum PCSK9 levels remained within normal ranges in both sexes. It can be hypothesized that blocking PCSK9 may further reduce serum cholesterol levels, which may have adverse effects in male patients with active IBD.